2021
DOI: 10.1155/2021/9630285
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Problem-Based Learning versus Traditional Teaching Methods in Improving Acquisition of Radiographic Interpretation Skills among Dental Students—A Systematic Review and Meta-Analysis

Abstract: Problem-based learning is an experiential and student-centred learning method to practice important skills like querying, critical thinking, and collaboration through pair and group work. The study is aimed at comparing the effectiveness of problem-based learning (PBL) and traditional teaching (TT) methods in improving acquisition of radiographic interpretation skills among dental students. Clinical trials (randomized and nonrandomized) were conducted with the help of dental students studying oral radiology us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(241 reference statements)
0
16
0
1
Order By: Relevance
“…In other words, PBL can not only improve students' professional skills through learning, but also exercise their ability to express themselves through presentations, improve their ability to conduct scientific research through literature retrieval, cultivate their clinical thinking through a comprehensive analysis of clinical cases, improve their capacity for teamwork through group discussion, and so forth. (Grupel et al, 2022; Luke et al, 2021; Wang et al, 2021). However, measurements and questionnaires alone cannot serve to evaluate all these teaching effects accurately and objectively.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, PBL can not only improve students' professional skills through learning, but also exercise their ability to express themselves through presentations, improve their ability to conduct scientific research through literature retrieval, cultivate their clinical thinking through a comprehensive analysis of clinical cases, improve their capacity for teamwork through group discussion, and so forth. (Grupel et al, 2022; Luke et al, 2021; Wang et al, 2021). However, measurements and questionnaires alone cannot serve to evaluate all these teaching effects accurately and objectively.…”
Section: Discussionmentioning
confidence: 99%
“…•instances of attribute: 20% •occurrences: 23,24,25,30,34,35,36,38,45,41,57,62,78,85 •Modified problem-based learning is the new norm in health services •Active learning methods in an online environment, with time, effort and scalability in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that interactive teaching mode was as excellent as conventional teaching methods, and in certain trials, it was proven to be the most effective learning approach [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Compared to traditional teaching approaches, interactive teaching has a considerable impact on cognitive achievement and learning attitude.…”
Section: Discussionmentioning
confidence: 99%